Hubungan Efikasi Diri terhadap Kepatuhan Perawatan Kaki Diabetes Melitus pada Masa Pandemi - Ela Susilawati; Refi Prananing Putri Hesi; Resna A Soerawidjaja (Universitas Faletehan, 2021)
Self-efficacy is one of the driving factors in carrying out diabetes mellitus management compliance behavior in performing foot care to prevent from the occurrence of amputation complications. Nevertheless, during the pandemic the attention of diabetes mellitus sufferers focused on covid-19 prevention. This study aims to determine the relationship between self-efficacy and foot care compliance in patients with diabetes mellitus. This research method was quantitative with a cross sectional study design. The samples were 39 people with diabetes mellitus who were selected by purposive sampling technique. The measuring instruments used were Foot Care Confidence Scale and Notthingham Assessment of Functional Foot Care. The data analysis used chi square test. The respondents' self-efficacy was good (56.4%) and their foot care compliance achieved 76.9% with the bivariate test of P-value 0.026. Self-efficacy has a relationship with foot care compliance of patients with diabetes mellitus.